REPRESENTASI PATRIARKI DARI SUDUT PANDANG TEORI STRUKTURAL-FUNGSIONALISME TOKOH-TOKOH DALAM FILM 7 HATI 7 CINTA 7 WANITA - Victor Efenly; John R Lahade (Universitas Kristen Satya Wacana, 2013)
Gender issues especially about womans is one of interest topic that be appointed in Indonesian cinemas. One of movie that takes on woman’s issues is created by new director, his name is Robby Ertanto Soediskam. It’s title is “7 Hati 7 Cinta 7 Wanita” (in English: 7 Heart 7 Love 7 Womans). This movie has interested attention from viewers and also cinema observers, it is because quality of story line and messages that be submited by director. This case be evidenced with several awards that be achieved in “Festival Film Indonesia 2010” and Indonesian Movie Awards 2011. Through content analysis methods, this research is trying to explain patriarch representation of “7 Hati 7 Cinta 7 Wanita” (in English: 7 Heart 7 Love 7 Womans) movie’s figures from view point of structural-fungsionalism theory. This research be implemented by observe woman’s figures then analyze them with structural-fungsionalism theory. The conclusion that be discovered is not all of case that happens between woman and man figures in this film is effected by patriarch system, such as previous research said. Structural-fungsionalism theory used can prove that patriarch system doesn’t cause oppresion and violence for woman. However, they are effect from role and function that isn’t implemented. Keywords: Gender, Woman, Patriarch, Structural-Fungsionalism, Representation, Film, Movie, 7 Hati 7 Cinta 7 Wanita